2016
DOI: 10.1016/j.celrep.2016.06.101
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-92 Cluster Regulates Adult Hippocampal Neurogenesis, Anxiety, and Depression

Abstract: Summary Emerging evidence has shown that noncoding RNAs, particularly microRNAs (miRNAs), contribute to the pathogenesis of mood and anxiety disorders, although the molecular mechanisms are poorly understood. Here we show altered levels of miR-17-92 in adult hippocampal neural progenitors have a significant impact on neurogenesis and anxiety- and depression-related behaviors in mice. miR-17-92 deletion in adult neural progenitors decreases neurogenesis in the dentate gyrus, while its overexpression increases n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 46 publications
3
87
1
Order By: Relevance
“…Depression resulting from miR-17∼92 knockout in adult NPCs 20 is a frequently occurring symptom in SZ patients 53 . Epilepsy, which often results in mis-localized adult-born neurons in the GCL, is a known risk factor for SZ 54-56 .…”
Section: Implications Of Mir-19 In Szmentioning
confidence: 99%
“…Depression resulting from miR-17∼92 knockout in adult NPCs 20 is a frequently occurring symptom in SZ patients 53 . Epilepsy, which often results in mis-localized adult-born neurons in the GCL, is a known risk factor for SZ 54-56 .…”
Section: Implications Of Mir-19 In Szmentioning
confidence: 99%
“…The primer used for mutagenesis was: miR-19a-mut, 5’–GCA GCC CTC TGT TAG TTT TGC ATA GTA GAG TAC AAG AAG AAT GTA GTT CTA CTA ATC TAT CAA AAC TGA TGG TGG CCT GC–3’. To generate miRNA expression constructs, miR-19a fragment was inserted into the pcDNA3.1 as described [18, 19]. Plasmids were quantified by Nanodrop 2000c Spec-trophotometer (Thermo Fisher Scientific, USA), and then transfected into 293T cells using Lipofectamine 3000 (Invitrogen, USA) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence has shown that this cluster is essential for many developmental and pathogenic processes [15], such as type B lymphopoiesis [16], lung development [16], heart development [17], neurogenesis [18, 19] and tumorigenesis [20]. It is involved in the processes of cell proliferation, apoptosis, differentiation and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have demonstrated a causal role for specific miRNAs in mediating stress coping behavior. Mice with miR-17–92 knocked out display increased reactive coping on forced-swim and tail-suspension tests [46], while mice with miR-34 knocked out display resilience to chronic mild stress [47]. However, none of these genetic manipulations have yet to take into account region-specific miRNA expression.…”
Section: Introductionmentioning
confidence: 99%